Comentario a la sentencia 05680-2009-PA/TC. Una necesaria aclaración sobre el modelo peruano de relaciones Iglesia – Estado - Mosquera Monelos, Susana (Revista de Derecho, 2020)
Using a commentary to the Constitutional Court last sentence, this paper will try to solve some questions about religious affairs. However the Constitution recognizes and protects freedom of religion, the use of this concept is not jet a pacific one, es-pecially when it is necessary to solve questions related with the Peruvian church and state relationship model. Freedom of religion and non establishment clause, a duet not always well performed.
Keywords: Freedom of conscience; freedom of religion; religious discrimination; church and state cooperation; non establishment clause